2016
DOI: 10.3130/jaabe.15.25
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Housing Modifications in Resettlement Sites in Cagayan de Oro, Philippines

Abstract: This study explores the reasons for, and patterns of, housing modifications in Mahogany Village at the Calaanan site, where permanent houses were built as part of a program to resettle communities affected by the severe tropical storm Washi that hit Cagayan de Oro City in December 2011. The basic housing units provided were not intended to be modified and the possibilities for adaptations were limited. However, this research found that residents were willing to invest in the construction of complementary space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…Resettlement of impacted population and rebuilding of houses are the foci during the recovery period after tropical storms, hurricanes, and related floods. There are articles introducing the modification of houses [143], the inadequate support from local governments [144] and incompatibility of supply and demand [145], interactions of stakeholders during the processes [146], as well as the necessity to adapt recovery projects to local conditions [147]. Despite the urgent need for resettling after wind hazards, scientists noticed the environmental impacts of temporary housing during the recovery period [148].…”
Section: Plos Onementioning
confidence: 99%
“…Resettlement of impacted population and rebuilding of houses are the foci during the recovery period after tropical storms, hurricanes, and related floods. There are articles introducing the modification of houses [143], the inadequate support from local governments [144] and incompatibility of supply and demand [145], interactions of stakeholders during the processes [146], as well as the necessity to adapt recovery projects to local conditions [147]. Despite the urgent need for resettling after wind hazards, scientists noticed the environmental impacts of temporary housing during the recovery period [148].…”
Section: Plos Onementioning
confidence: 99%
“…As a result, relocation initiatives meet with resistance because of the introduction of top‐down approaches (donor‐ and owner‐driven reconstruction, for instance) to tackle housing concerns (Karunasena and Rameezdeen, 2010; Schilderman and Lyons, 2011). Given the restricted avenues for community consultation and participation, policy planners regularly fail to ‘integrate local characteristics and [the] pre‐disaster context of resettled communities’ after the initial planning stage (Carrasco, Ochiai, and Okazaki, 2016, p. 25). As Davidson et al (2007, p. 113) note, though, ‘it seems to be pointless to try to determine once and for all the optimum nature and role of community participation—per se—in a reconstruction project.…”
Section: Post‐disaster Relocation and Resettlementmentioning
confidence: 99%
“…The reasons behind the residents' implementation of extensions and renovations include the fact that many have a small income, and most want to run a store; by extending their houses they can facilitate a Filipino traditional outdoor kitchen called a "Dirty Kitchen." (Carrasco et al, 2016a) Considering the residence-environment-related requests of the residents, such extensions are inevitable, and it can be concluded that the provision of appropriate houses and the establishment of resolutions that fit regional characteristics are necessary. (Carrasco et al, 2016b) However, there are also dangers associated with these extensions and renovations, as the materials used can have poor durability.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Previous surveys have already investigated the condition of the extended/renovated housing and the attributes of residents at several resettlement sites in the Philippines (Carrasco et al, 2016a). However, the construction systems used for extensions and renovations (i.e., the manner by which people at resettlement sites conduct the extension and renovation of their housing) are not yet fully understood, nor is their influence on the condition of housing and the lives of the residents.…”
Section: Introduction 11 Background and Purposementioning
confidence: 99%